Understanding Facebook news post comment reading and reacting behavior through political extremism and cultural orientation. (November 2019) - Almoqbel, Mashael Y.; Wohn, Donghee Yvette; Hayes, Rebecca A.; Cha, Meeyoung
Abstract: Social media allows the readers of online news posts more engagement with the article through comments and comment Liking. Motivations for such actions are important because engagement around a comment increases the accessibility of that comment to other readers, leading to a far-reaching effect on the news post ground truth. Yet, motivations behind these actions and how they relate to the increasingly polarized political environment is understudied. This research investigates motivations for comment reading and Liking on social media news articles, and whether reading comments before or after reading the full article is related to different commenting and Liking motivations. In addition, we examine how political extremism and cultural orientation is related to users' motivations. Through survey data (N = 514) obtained from two samples, one Korean and one in the U.S., we conclude that cultural orientation was a salient independent variable when looking at comment and Liking motivations, while political extremism played a minor role in motivations. Highlights: Commenting and Liking comments motivations on social media news posts are presented. Cultural orientations play a salient role in online news posts commenting decisions. Commenting and Liking features appeal more to individualists. Comments on online news posts were used as cues to decide to read news posts or not.